Pioneers in Nordic sociology of law - Hyden, Hakan (2013)
Sociology of Law in the Nordic countries mainly grew up in the postwar period. It was associated with the beginnings of the welfare state establishment. Those mainly to be counted as pioneers are Vilhelm Aubert (1922-1988), Per Stjernquist (1912-2005) and Agnete Weis Bentzon (1918 -). Aubert dealt with topics as conflict resolution, equality before the law and the legal profession. Stjernquist´s main interest was about law as a political instrument. Weis Bentzon´s main contribution is related to laying the foundation for regulation of the Greenlandic society through a survey of the customs of the people of Greenland. Finally there is reason to mention Theodor Geiger (1891-1952), although he did not play the same role for the development of the Nordic Sociology of Law as the German. Geiger argued for including social norms for the understanding of social cohesion. The article presents the work of these scholars.